Experimental Study on the Effect of Single and Double Quenching-Tempering on the Mechanical Properties of AISI 1045 Steel - Syaipudin Anwar; Harnowo Supriadi; Nafrizal; Rizal Adi Saputra; Andree Agasy Nofma (RING ME, 2026)
This study examined the effects of quenching, single quenching–tempering (SQT), and double quenching–tempering (DQT) on the microstructure and mechanical properties of AISI 1045 medium-carbon steel (0.54% C, 0.32% Si, 0.65% Mn, 0.015% P, 0.0112% S, balance Fe). All specimens were heated to 850°C for 25 minutes and quenched in coconut oil at 100°C. Tempering was subsequently performed at 650°C for the SQT and DQT treatments. Hardness testing revealed that quenching produced the highest hardness value of 242.38 kg/mm² due to the formation of martensite. The SQT treatment reduced hardness to 198.46 kg/mm², indicating improved toughness while maintaining relatively high hardness. Further reduction in hardness was observed in the DQT-treated specimens, reaching 158.13 kg/mm², reflecting a more ductile and tougher microstructure. Impact properties were evaluated using the Charpy method. Heat-treated specimens exhibited significantly higher impact strength than the untreated material. The SQT process increased impact strength to 1.5792 J/mm², demonstrating the beneficial effect of tempering on toughness. The highest impact strength was achieved through DQT, reaching 1.8542 J/mm², indicating superior energy absorption capability. The results show that repeated quenching and tempering cycles effectively enhance the toughness of AISI 1045 steel, although accompanied by a reduction in hardness. Overall, DQT provided the best improvement in impact resistance and toughness among the heat treatment conditions investigated.